Beta-catenin signaling plays a disparate role in different phases of fracture repair: implications for therapy to improve bone healing. - Yan Chen (PLoS Medicine, 2007)
BACKGROUND: Delayed fracture healing causes substantial disability and usually requires additional surgical treatments. Pharmacologic management to improve fracture repair would substantially improve patient outcome. The signaling pathways regulating bone healing are beginning to be unraveled, and they provide clues into pharmacologic management. The beta-catenin signaling pathway, which activates T cell factor (TCF)-dependent transcription, has emerged as a key regulator in embryonic skeletogenesis, positively regulating osteoblasts. However, its role in bone repair is unknown. The goal of this study was to explore the role of beta-catenin signaling in bone repair. METHODS AND FINDINGS: Western blot analysis showed significant up-regulation of beta-catenin during the bone healing process. Using a beta-Gal activity assay to observe activation during healing of tibia fractures in a transgenic mouse model expressing a TCF reporter, we found that beta-catenin-mediated, TCF-dependent transcription was activated in both bone and cartilage formation during fracture repair. Using reverse transcription-PCR, we observed that several WNT ligands were expressed during fracture repair. Treatment with DKK1 (an antagonist of WNT/beta-catenin pathway) inhibited beta-catenin signaling and the healing process, suggesting that WNT ligands regulate beta-catenin. Healing was significantly repressed in mice conditionally expressing either null or stabilized beta-catenin alleles induced by an adenovirus expressing Cre recombinase. Fracture repair was also inhibited in mice expressing osteoblast-specific beta-catenin null alleles. In stark contrast, there was dramatically enhanced bone healing in mice expressing an activated form of beta-catenin, whose expression was restricted to osteoblasts. Treating mice with lithium activated beta-catenin in the healing fracture, but healing was enhanced only when treatment was started subsequent to the fracture. CONCLUSIONS: These results demonstrate that beta-catenin functions differently at different stages of fracture repair. In early stages, precise regulation of beta-catenin is required for pluripotent mesenchymal cells to differentiate to either osteoblasts or chondrocytes. Once these undifferentiated cells have become committed to the osteoblast lineage, beta-catenin positively regulates osteoblasts. This is a different function for beta-catenin than has previously been reported during development. Activation of beta-catenin by lithium treatment has potential to improve fracture healing, but only when utilized in later phases of repair, after mesenchymal cells have become committed to the osteoblast lineage.